Development spotlight - Brazil - Digel, H. (New Studies in Athletics, 2011)
From the point of view of organisation, the development of athletics is a global success story. Europe has played a dominant role, both in terms of governance and competition results but with the end of colonialism and, later, the break up of the Soviet empire, the distribution of top performers has changed. The author, an IAAF Council member and a former national federation president, outlines the positive development of performances and their spread around the globe. He also notes that in many aspects the sport is still a patchwork of positive and negative stories. However, there are a number of shining examples that should be learned from. One of these is Brazil, where since 1987 the federation has developed its governance and management structures, been a catalyst for the creation of new tracks and other infrastructure, staged many international events and led a phenomenal increase in performance levels. After detailing the country`s various successes, the author concludes with the hope that the federation will continue on its path and profit from the staging of the 2016 Olympic Games in Rio de Janeiro.